HUMAN CAPITAL AND LEADERSHIP AS DRIVERS OF COOPERATIVE PERFORMANCE: A CONCEPTUAL - Mohd Noor, Azianis; Ismail, Mohammad; Azmi, Siti Nurulaini; Zawawi, Nur Fadiah Mohd; Mohamad, Nurul Muna; Sidik, Mohamad Hazeem (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This conceptual paper develops a cross-context framework explaining how human capital influences cooperative performance, with leadership acting as a moderating factor across diverse cooperative environments. Anchored in the Human Capital Theory (HCT) and the Resource-Based View (RBV) theory, the paper conceptualises knowledge, skills, and experience as strategic resources that enhance cooperatives' financial, social, and governance outcomes. Drawing on evidence from Malaysia and comparative insights from Vietnam, Ethiopia, and other international settings, the model proposes that leadership, particularly transformational, participative, and servant styles, serves as a dynamic capability that activates and aligns human capital for sustainable performance. The framework advances theoretical understanding by positioning leadership as an orchestration mechanism within RBV, transforming HC into sustained cooperative advantage. Practically, it guides policymakers and cooperative boards to strengthen leadership development, digital readiness, and knowledge-sharing ecosystems. Socially, it underscores cooperatives' role in promoting inclusive growth, community resilience, and sustainable livelihoods, aligning with global Sustainable Development Goals (SDGs).